UPAYA GREEN PEACE MENGHENTIKAN ILLEGAL FISHING DI THAILAND - Aldian Febris Adhiwidjaya; Irwan Iskandar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
One of the major maritime security issue for many countries in the world is Illegal, Unreported and Unregulated Fishing (IUU Fishing) on the sea. IUU Fishing is a non-traditional security issue that have become an important concern for many countries, due to serious impactThis research using constructivism perspective and using international organization theory and institutionalism theory as the additional theory. The level of analysis is group of actors and this research using descriptive-qualitative methods, and observation as the data collecting.This research shows that Thailand Government must supervise the IUU cases and if the government failed, it will be affecting the huge political crisis. Greenpeace requests to government of Thailand to revise the certain related policies in order of effectiveness.Keywords: IUU, Thailand, Greenpeace, Maritime, Not Just Tun